Preferential solvation drives polysaccharide conformation and viscoelasticity - Pallab Kumar Borah; Joshua E.S.J. Reid; Thomas MacCalman; Amir H. Irani; Daniela Russo; Jens Smiatek; Johannes Hunger; Mona Sarter; Vlad Dinu; Francesca Natali; Michael Boehm; Stephen E. Harding; et al. (Carbohydrate Polymers, 2026)

Developing high-concentration monoclonal antibody formulations for subcutaneous administration to improve patient treatment - Laura R. R. Mijangos; Stephen E. Harding; Nicholas J. Darton (Biophysical Reviews, 2025)
The transition of immunotherapy administration from intravenous infusion to subcutaneous (SC) administration of monoclonal antibody formulations for oncology patients has garnered significant interest. SC administration offers multiple benefits, including potential for at-home administration, enhanced patient compliance, reduced hospital congestion, lowered health care costs, and improved sustainability by reducing drug wastage and minimizing environmental impact. However, for many biologics, the shift to SC administration requires the development of high-concentration monoclonal antibody products (HCmAP) due to the need for large dose volumes. Here we explore the impact of the COVID-19 pandemic on immunotherapy administration and the imperative of adopting SC administration. We discuss challenges encountered throughout the manufacturing, shipping, storage, and delivery of HCmAP. A central hurdle identified involves the biophysical instability and the large increase in viscosity of these biologics due to increased antibody concentration. Further complications can arise from “non-ideality” effects through molecular crowding or co-exclusion effects (macromolecules blocking the free movement in solution of other macromolecules) and elevated macromolecular interactions. For reducing the viscosity for a given concentration of antibody, the main excipients reported are salts and amino acids, with Arg-HCl demonstrating particularly improved formulation viscosity in an HCmAP. However, excipients with viscosity-lowering effects can also impact protein stability. The journey to discover suitable excipient strategies remains ongoing, combined with emerging approaches such as molecular engineering and computational techniques, with the ultimate aim of facilitating the successful integration of SC administration for economic savings, environmental sustainability, and social equity.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Influence of ripening stage on the microwave-assisted pectin extraction from banana peels: A feasibility study targeting both the Homogalacturonan and Rhamnogalacturonan-I region - Yujie Mao; Shinta R. Dewi; Stephen E. Harding; Eleanor Binner (Food Chemistry, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

An obituary: Dr. Helmut Cölfen 1965–2023 - Borries Demeler; Denis Gebauer; Emre Brookes; Jeffrey Fagan; Johannes Walter; José García de la Torre; Juan Manuel García-Ruiz; Kristian Schilling; Mengdi Chen; Lukas Dobler; Olwyn Byron; Stephen E. Harding; et al. (European Biophysics Journal, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Experimental support for reclassification of the light scattering second virial coefficient from macromolecular solutions as a hydrodynamic parameter - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This investigation examines the source of the disparity between experimental values of the light scattering second virial coefficient $${A}_{2}$$ A 2 (mL.mol/g 2 ) for proteins and those predicted on the statistical mechanical basis of excluded volume. A much better theoretical description of published results for lysozyme is obtained by considering the experimental parameters to monitor the difference between the thermodynamic excluded volume term and its hydrodynamic counterpart. This involves a combination of parameters quantifying concentration dependence of the translational diffusion coefficient obtained from dynamic light scattering measurements. That finding is shown to account for observations of a strong correlation between $${A}_{2}{M}_{2}$$ A 2 M 2 (mL/g), where M 2 is the molar mass (molecular weight) of the macromolecule and the diffusion concentration parameter $${k}_{D}$$ k D (mL/g). On the grounds that $${k}_{D}$$ k D is regarded as a hydrodynamic parameter, the same status should be accorded the light scattering second virial coefficient rather than its current incorrect thermodynamic designation as $${B}_{2}$$ B 2 (mL.mol/g 2 ), or just B , the osmotic second virial coefficient for protein self-interaction.

Retrospective rationalization of disparities between the concentration dependence of diffusion coefficients obtained by boundary spreading and dynamic light scattering - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This study establishes the existence of substantial agreement between published results from traditional boundary spreading measurements (including synthetic boundary measurements in the analytical ultracenrifuge) on two globular proteins (bovine serum albumin, ovalbumin) and the concentration dependence of diffusion coefficient predicted for experiments conducted under the operative thermodynamic constraints of constant temperature and solvent chemical potential. Although slight negative concentration dependence of the translational diffusion coefficient is the experimentally observed as well as theoretically predicted, the extent of the concentration dependence is within the limits of experimental uncertainty inherent in diffusion coefficient measurement. Attention is then directed toward the ionic strength dependence of the concentration dependence coefficient ( $${k}_{D}$$ k D ) describing diffusion coefficients obtained by dynamic light scattering, where, in principle, the operative thermodynamic constraints of constant temperature and pressure preclude consideration of results in terms of single-solute theory. Nevertheless, good agreement between predicted and published experimental ionic strength dependencies of $${k}_{D}$$ k D for lysozyme and an immunoglobulin is observed by a minor adaptation of the theoretical treatment to accommodate the fact that thermodynamic activity is monitored on the molal concentration scale because of the constraint of constant pressure that pertains in dynamic light scattering experiments.

Comparative sedimentation equilibrium analysis of two IgG1 glycoforms: IgGCri and IgGWid - Khalil Abu Hammad; Vlad Dinu; Thomas E. MacCalman; Jacob Pattem; Margaret Goodall; Richard B. Gillis; Roy Jefferis; Stephen E. Harding (European Biophysics Journal, 2023)
The solution properties of two different glycoforms of IgG1 (IgG1Cri and IgG1Wid) are compared using primarily sedimentation equilibrium analysis with two complementary analysis routines: SEDFIT-MSTAR and MULTISIG. IgGCri bears diantennary complex-type glycans on its Fc domain that are fully core fucosylated and partially sialylated, whilst on IgGWid, they are non-fucosylated, partially galactosylated and non-sialylated. IgGWid is also Fab glycosylated. Despite these differences, SEDFIT-MSTAR analysis shows similar weight average molar masses M w of ~ (150 ± 5) kDa for IgGCri and ~ (154 ± 5) kDa for IgGWid and both glycoforms show evidence of the presence of a small fraction of dimer confirmed by MULTISIG analysis and also by sedimentation coefficient distributions from supportive sedimentation velocity measurements. The closeness of the sedimentation equilibrium behaviour and sedimentation coefficient distributions with a main peak sedimentation coefficient of ~ 6.4S for both glycoforms at different concentrations suggest that the different glycosylation profiles do not significantly impact on molar mass (molecular weight) nor conformation in solution.

Strong non-ideality effects at low protein concentrations: considerations for elongated proteins - Alexander E. Yarawsky; Vlad Dinu; Stephen E. Harding; Andrew B. Herr (European Biophysics Journal, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Biophysical Reviews’ “meet the editors series”—a profile of Steve Harding’s career in macromolecular hydrodynamics - Stephen E. Harding (Biophysical Reviews, 2022)

Quantifying the concentration dependence of sedimentation coefficients for globular macromolecules: a continuing age-old problem - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (Biophysical Reviews, 2021)
This retrospective investigation has established that the early theoretical attempts to directly incorporate the consequences of radial dilution into expressions for variation of the sedimentation coefficient as a function of the loading concentration in sedimentation velocity experiments require concentration distributions exhibiting far greater precision than that achieved by the optical systems of past and current analytical ultracentrifuges. In terms of current methods of sedimentation coefficient measurement, until such improvement is made, the simplest procedure for quantifying linear s - c dependence (or linear concentration dependence of 1/ s ) for dilute systems therefore entails consideration of the sedimentation coefficient obtained by standard c ( s ), g* ( s ) or G ( s ) analysis) as an average parameter ( $$ \overline{s} $$ s ¯ ) that pertains to the corresponding mean plateau concentration (following radial dilution) ( $$ \overline{c} $$ c ¯ ) over the range of sedimentation velocity distributions used for the determination of $$ \overline{s} $$ s ¯ . The relation of this with current descriptions of the concentration dependence of the sedimentation and translational diffusion coefficients is considered, together with a suggestion for the necessary improvement in the optical system.

Glycoconjugate vaccines against Salmonella enterica serovars and Shigella species: existing and emerging methods for their analysis - Aleksandra Bazhenova; Fang Gao; Barbara Bolgiano; Stephen E. Harding (Biophysical Reviews, 2021)
The global spread of enteric disease, the increasingly limited options for antimicrobial treatment and the need for effective eradication programs have resulted in an increased demand for glycoconjugate enteric vaccines, made with carbohydrate-based membrane components of the pathogen, and their precise characterisation. A set of physico-chemical and immunological tests are employed for complete vaccine characterisation and to ensure their consistency, potency, safety and stability, following the relevant World Health Organization and Pharmacopoeia guidelines. Variable requirements for analytical methods are linked to conjugate structure, carrier protein nature and size and O- acetyl content of polysaccharide. We investigated a key stability-indicating method which measures the percent free saccharide of Salmonella enterica subspecies enterica serovar Typhi capsular polysaccharide, by detergent precipitation, depolymerisation and HPAEC-PAD quantitation. Together with modern computational approaches, a more precise design of glycoconjugates is possible, allowing for improvements in solubility, structural conformation and stability, and immunogenicity of antigens, which may be applicable to a broad spectrum of vaccines. More validation experiments are required to establish the most effective and suitable methods for glycoconjugate analysis to bring uniformity to the existing protocols, although the need for product-specific approaches will apply, especially for the more complex vaccines. An overview of current and emerging analytical approaches for the characterisation of vaccines against Salmonella Typhi and Shigella species is described in this paper. This study should aid the development and licensing of new glycoconjugate vaccines aimed at the prevention of enteric diseases.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Probing the effect of aroma compounds on the hydrodynamic properties of mucin glycoproteins - Vlad Dinu; Thomas MacCalman; Ni Yang; Gary G. Adams; Gleb E. Yakubov; Stephen E. Harding; Ian D. Fisk (European Biophysics Journal, 2020)
Aroma compounds are diverse low molecular weight organic molecules responsible for the flavour of food, medicines or cosmetics. Natural and artificial aroma compounds are manufactured and used by the industry to enhance the flavour and fragrance of products. While the low concentrations of aroma compounds present in food may leave no effect on the structural integrity of the mucosa, the effect of concentrated aroma volatiles is not well understood. At high concentrations, like those found in some flavoured products such as e-cigarettes, some aroma compounds are suggested to elicit a certain degree of change in the mucin glycoprotein network, depending on their functional group. These effects are particularly associated with carbonyl compounds such as aldehydes and ketones, but also phenols which may interact with mucin and other glycoproteins through other interaction mechanisms. This study demonstrates the formation of such interactions in vitro through the use of molecular hydrodynamics. Sedimentation velocity studies reveal that the strength of the carbonyl compound interaction is influenced by compound hydrophobicity, in which the more reactive short chain compounds show the largest increase in mucin-aroma sedimentation coefficients. By contrast, the presence of groups that increases the steric hindrance of the carbonyl group, such as ketones, produced a milder effect. The interaction effects were further demonstrated for hexanal using size exclusion chromatography light scattering (SEC-MALS) and intrinsic viscosity. In addition, phenolic aroma compounds were identified to reduce the sedimentation coefficient of mucin, which is consistent with interactions in the non-glycosylated mucin region.

Tert-butyldimethylsilyl chitosan synthesis and characterization by analytical ultracentrifugation, for archaeological wood conservation - Jennifer M. K. Wakefield; Susan Braovac; Hartmut Kutzke; Robert A. Stockman; Stephen E. Harding (European Biophysics Journal, 2020)
The Oseberg ship is one of the most important archaeological testimonies of the Vikings. After excavation in 1904, the wooden gravegoods were conserved using alum salts. This resulted in extreme degradation of a number of the objects a hundred years later through acid depolymerisation of cellulose and lignin. The fragile condition of the artefacts requires a reconsolidation which has to be done avoiding water as solvent. We synthesized tert- butyldimethylsilyl (TBDMS) chitosan which is soluble in a 50:50 solution of ethyl acetate and toluene. Measurement of its molecular weight, to anticipate its penetration, provided a challenge as the density difference of the polymer and solvent was too small to provide adequate solute redistribution under a centrifugal field, so a two-stage process was implemented (i) determination of the weight-average molar mass of the aqueous soluble activated precursor, chitosan mesylate, M w,mc using sedimentation equilibrium with the SEDFIT-MSTAR algorithm, and determination of the degree of polymerisation DP ; (ii) measurement of the average degree of substitution DS TBDMS of the TBDMS group on each chitosan monosaccharide monomer unit using NMR, to augment the M w,mc value to give the molar mass of the TBDMS-chitosan. For the preparation, we find M w = 9.8 kg·mol −1 , which is within the acceptable limit for penetration and consolidation of degraded wood. Future work will test this on archaeological wood from different sources.

Aminoethyl substitution enhances the self-assembly properties of an aminocellulose as a potential archaeological wood consolidant - Jennifer M. K. Wakefield; Robert Hampe; Richard B. Gillis; Agnes Sitterli; Gary G. Adams; Hartmut Kutzke; Thomas Heinze; Stephen E. Harding (European Biophysics Journal, 2020)
The 6-deoxy-6-aminocelluloses—or “aminocelluloses”—are a class of synthetic natural cellulose derivatives which are mostly aqueous soluble and have excellent film-forming properties. Recent studies have connected these properties at the molecular level with protein-like self-associative behaviour for a range of aminocelluloses including a 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1 with the association being a two-stage process—a reversible oligomerisation followed by further (semi-reversible) aggregation into larger structures. Here, we synthesise and compare a new 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1′ with different degree of substitution with one with further alkyl derivatisation, namely 6-deoxy-6-(ω-hydroxyethyl) aminocellulose HEA-1′. As with AEA-1, sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge still show a two-stage process for both AEA-1′ and HEA-1′, with the latter giving higher molar masses. The consequences of these properties for use as consolidants for archaeological wood are considered.

A simple cell-alignment protocol for sedimentation velocity analytical ultracentrifugation to complement mechanical and optical alignment procedures - Guy Channell; Vlad Dinu; Gary G. Adams; Stephen E. Harding (European Biophysics Journal, 2018)

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

The Svedberg Lecture 2017. From nano to micro: the huge dynamic range of the analytical ultracentrifuge for characterising the sizes, shapes and interactions of molecules and assemblies in Biochemistry and Polymer Science - Stephen E. Harding (European Biophysics Journal, 2018)

Controlled depolymerisation assessed by analytical ultracentrifugation of low molecular weight chitosan for use in archaeological conservation - Jennifer M. K. Wakefield; Richard B. Gillis; Gary G. Adams; Caitlin M. A. McQueen; Stephen E. Harding (European Biophysics Journal, 2018)

Interaction studies of a protein and carbohydrate system using an integrated approach: a case study of the miniagrin–heparin system - Trushar R. Patel; Tabot M. D. Besong; Markus Meier; Kevin McEleney; Stephen E. Harding; Donald J. Winzor; Jörg Stetefeld (European Biophysics Journal, 2018)

Antimicrobial resistance (AMR) nanomachines—mechanisms for fluoroquinolone and glycopeptide recognition, efflux and/or deactivation - Mary K. Phillips-Jones; Stephen E. Harding (Biophysical Reviews, 2018)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Assessing sedimentation equilibrium profiles in analytical ultracentrifugation experiments on macromolecules: from simple average molecular weight analysis to molecular weight distribution and interaction analysis - Stephen E. Harding; Richard B. Gillis; Gary G. Adams (Biophysical Reviews, 2016)

Foreword to ‘Quantitative and analytical relations in biochemistry’—a special issue in honour of Donald J. Winzor’s 80th birthday - Damien Hall; Stephen E. Harding (Biophysical Reviews, 2016)

Application of recent advances in hydrodynamic methods for characterising mucins in solution - Fahad M. Almutairi; Jose-Gines Hernandez Cifre; Gary G. Adams; M. Samil Kök; Alan R. Mackie; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2016)

The Hypoglycemic Effect of Pumpkin Seeds, Trigonelline (TRG), Nicotinic Acid (NA), and D-Chiro-inositol (DCI) in Controlling Glycemic Levels in Diabetes Mellitus - Gary G. Adams; Shahwar Imran; Sheng Wang; Abubaker Mohammad; M. Samil Kok; David A. Gray; Guy A. Channell; Stephen E. Harding (Critical Reviews in Food Science and Nutrition, 2014)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Hydrodynamic modelling of protein conformation in solution: ELLIPS and HYDRO - José García de la Torre; Stephen E. Harding (Biophysical Reviews, 2013)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Correlation of SEC/MALLS with ultracentrifuge and viscometric data for chitosans - Monica Fee; Neil Errington; Kornelia Jumel; Lisbeth Illum; Alan Smith; Stephen E. Harding (European Biophysics Journal, 2003)

Estimating domain orientation of two human antibody IgG4 chimeras by crystallohydrodynamics - Emma Longman; Katja Kreusel; Saul B. Tendler; Immo Fiebrig; Kevin King; John Adair; Paul O'Shea; Alvaro Ortega; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2003)

A comparison of molecular mass determination of hyaluronic acid using SEC/MALLS and sedimentation equilibrium - Sanya Hokputsa; Kornelia Jumel; Catherine Alexander; Stephen E. Harding (European Biophysics Journal, 2003)

Trp203 mutation in GroEL promotes a self-association reaction: a hydrodynamic study - Chris Walters; Anthony Clarke; Matthew J. Cliff; Peter A. Lund; Stephen E. Harding (European Biophysics Journal, 2000)

Calculation of NMR relaxation, covolume, and scattering-related properties of bead models using the SOLPRO computer program - J. García de la Torre; Stephen E. Harding; Beatriz Carrasco (European Biophysics Journal, 1999)

Hydrodynamic properties of mucins secreted by primary cultures of Guinea-pig tracheal epithelial cells: determination of diffusion coefficients by analytical ultracentrifugation and kinetic analysis of mucus gel hydration and dissolution - Sara Dodd; Graham A. Place; R. L. Hall; Stephen E. Harding (European Biophysics Journal, 1998)

Ultracentrifugation studies on the transmembrane domain of the human erythrocyte anion transporter Band 3 in the detergent C 12 E 8 - H. Cölfen; J. M. Boulter; Stephen E. Harding; Anthony Watts (European Biophysics Journal, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Alteration of the quaternary structure of glutamate dehydrogenase from Clostridium symbiosum by a single mutation distant from the subunit interfaces - Jonathan L. E. Dean; H. Cölfen; Stephen E. Harding; David W. Rice; P. C. Engel (European Biophysics Journal, 1997)

SOLPRO: theory and computer program for the prediction of SOLution PROperties of rigid macromolecules and bioparticles - J. García de la Torre; Beatriz Carrasco; Stephen E. Harding (European Biophysics Journal, 1997)

MSTARA and MSTARI: interactive PC algorithms for simple, model independent evaluation of sedimentation equilibrium data - H. Cölfen; Stephen E. Harding (European Biophysics Journal, 1997)

New developments in analytical ultracentrifugation and related macromolecular modelling techniques - O. Byron; Stephen E. Harding (European Biophysics Journal, 1997)